DESIGN AND IMPLEMENTATION OF AN IOT-BASED VOLUME MONITORING SYSTEM FOR A RECTANGULAR SOLID STRUCTURE - Andriany, Rara Chanesha Ismi; Yacoub, Redi Ratiandi; Sanjaya, Bomo Wibowo; Priyatman, Hendro; Saleh, Muhammad (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
The calculation of volume within a three-dimensional structure has the potential to determine its enclosed mass. This research aims to create a system that utilizes data from the HC-SR04 sensor to calculate volume, incorporating the Internet of Things (IoT) for remote monitoring. The study involves the use of HC-SR04 and DHT11 sensors to gather data on filled height and temperature. The measurement approach encompasses mathematical formulas for volume and surface area that correspond to the shape of the compartment. The ESP32 microcontroller serves as the central processing unit. Experimental trials are conducted, manipulating different height levels within the object. The results reveal differences between theoretical estimations and sensor-derived assessments, highlighted by varying outcomes in specific scenarios. The calculated volume of the filled compartment is displayed on OLED-1 and transmitted through the Blynk application. This study significantly contributes to the advancement of a sensor- and IoT-driven monitoring infrastructure, facilitating the observation of filled height and volume in physical objects. Despite certain variations observed in the trials, the outcomes consistently demonstrate minimal error rates.